Psychological Contracting Process Model: Towards A Unifying Theory Of Psychological Contract - Njenga, Francis Ndirangu (International Journal of Scientific Research and Management (IJSRM), 2017)
Although the concept of psychological contract was introduced in organization behavior more than fifty years ago, the proliferation of writings on the subject has yielded many definitions and measurements which threaten its explanatory power in social sciences. Indeed authors have evaded attempts on theory building including the phenomenology of the contracting process which would render validity to the construct. This article explains a model for the psychological contract process which aids us develop an epistemic definition as well as how the construct related to other concepts in the horizon. The approach involved knowledge blending of the disciplines of psycho-linguistics, law and social psychology. In psycholinguistic there are three conceptual fields such as perceptions, mind and thoughts. The mind sub-stream has language (communicative actions) as one of the components with language processing as sub component that yields the speech production for example performative acts. Speech acts have an overarching objective to persuade someone, make good impression or build trust and loyalty exchanges. The psychological contract process model articulated in this article comprise of contract cognitive effort/input phase, cognitive priming/instrumentation phase and cognitive state at priori domain of the contract. The input phase is an activity involving communicative action of undertaking to satisfy interest, desires, needs or goals of a referent other; followed by achievement of activation of expectations and then accomplishment level of satisfaction of the promise. Finally the posteriori domains comprise of the trust affection and loyalty behaviors as a consequent of the cognitive state. This process model will enable us distinguish between the notion of a contract as established in law, economics and sociology and that of psychological contract. Moreover it allows us move the current debate forward and towards a unifying theory of psychological contract.